Hyaluronic acid–targeted topotecan liposomes improve therapeutic efficacy against lung cancer in animals - Xue, Gangqiang; Tang, Lu; Pan, Xinyan; Li, Sanni; Zhao, Juan (Frontiers in Oncology, 2024)
Lung cancer, as a serious threat to human health and life, necessitating urgent treatment and intervention. In this study, we prepared hyaluronic acid (HA)-targeted topotecan liposomes for site-specific delivery to tumor cells. The encapsulation efficiency, stability, chemical structure, and morphology of HA-targeted topotecan liposomes were studied, and the release properties, cellular uptake capacity, and therapeutic efficacy of topotecan were further investigated. Results found that the coupling efficiency of HA on the surface of PEG-coated liposomes was determined to be 13.65 nmol/mg of lipid. The HA-targeted topotecan liposomes demonstrated a high encapsulation efficiency of 95% for topotecan, with an average particle size of 98.26 nm and excellent storage and dispersion stability. Drug release and cellular experiments indicated that the coating of HA further reduced the release rate of topotecan and decreased the survival rate of A549 cells, respectively. Flow cytometry and fluorescence staining analyses revealed that the HA-targeted topotecan liposomes enhanced the uptake of topotecan and exhibited significant anti-tumor effects on A549 cancer cells transplanted in mice. H&E staining showed that the pathological tissue treated with HA-targeted topotecan liposomes corresponded to Miller-Payne grade IV. Furthermore, these liposomes increased the accumulation of topotecan in tumors and extended the blood circulation time of the drug. Therefore, HA-targeted topotecan liposomes can be used as a new and easily prepared carrier in the field of lung chemotherapy, demonstrating considerable potential for anti-tumor therapy.